Gloss on the Supreme Administrative Court judgement of 25 November 2020, files No.: II OSK 1987/20 (Ius Novum, 2021)
The gloss discusses legal consequences of the approval of a general plan of a public airport.It concerns the necessity of suspending proceedings in the case of determining the conditionsof investment developments in the area covered by a general plan until the zoning schemeis adopted in accordance with this general plan. Approving of the stance expressed in thejudgement of the Supreme Administrative Court, the gloss also presents calls for amendmentsto the provisions of Act: Aviation Law concerning general plans of airports, as well as therelated provisions concerning areas limiting aviation obstacles. The author’s argumentsare based on the distinction between possible legal instruments laid down in aviation lawregulations in order to ensure the development of aviation infrastructure.
Keywords: general plan of an airport; public airport; local zoning; suspension of a proceeding concerning the determination of conditions of investment developments